Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

The next set of medium/hard PS algebra questions. I'll post OA's with detailed explanations after some discussion. Please, post your solutions along with the answers.

1. If \(x=\sqrt[4]{x^3+6x^2}\), then the sum of all possible solutions for x is:

1. x^4 = x^3 + 6x^2 => x^2 (x^2 - x - 6) = 0 The roots of x^2 - x - 6 are -2 and 3, but -2 cannot be the value of x. So 3 and 0 are the only possible roots. => Sum of all possible solutions = 3.

1. x^4 = x^3 + 6x^2 => x^2 (x^2 - x - 6) = 0 Sum of roots of x^2 - x - 6 = 0 is 1 and the only other solution is x=0 => Sum of all possible solutions = 1.

2. Let one of the roots be x, then other root is also x. Sum of roots = 2x = -a Product of roots = x^2 = - b

For other equation one root is 3 and product of the roots is 15, so other root is 5. Sum of roots = 8 = -a or a = -8. From above 2x = 8 or x = 4, b = - x^2 = -16. Answer is B.

3. a^2 + b^ 2 = m a^2 - b^2 = n Solving both the equations( adding them, and then subtracting them ): 2a^2 = m + n 2b^2 = m - n. a = ((m+n)/2)^(1/2) b = ((m-n)/2)^(1/2)

Now -x^2 +4x - 13 has its maximum value at x = -4/-2 = 2 and -y^2 - 6y has its maximum value at y=6/-2 = -3 Therefore max value of the expression = 3(-4 + 8 -13) + 2 (-9+18) = -27 + 18 = -9

Product of all n = product of roots of the above equation. For ax^2 + bx + c = 0 => Product of roors = c/a Product of roots = -145/1 = -145 Ans = A
_________________

"Appreciation is a wonderful thing. It makes what is excellent in others belong to us as well." ― Voltaire Press Kudos, if I have helped. Thanks!

1)\(x^4=x^3+6x^2\) \(x^4-x^3-6x^2=0\) \(x^2(x^2-x-6)=0\) \(x^2=0 (1) x = 0\) \(x^2-x-6=0 (2) x = 3 (3) x = -2\) \(0+3-2=1\) C

2)The equation x^2 + ax - b = 0 has equal roots \(a^2+4b=0\) one of the roots of the equation x^2 + ax + 15 = 0 is 3 \((-a+-\sqrt{a^2-4*15})/2=3\) \(+-\sqrt{a^2-60}=6+a\) \((\sqrt{a^2-60})^2=(6+a)^2\) \(-96=12a\) \(a=-8\)

\(a^2+4b=0\) \(64+4b=0\) \(b=-16\) B

3)We can use some numbers \(2^2+1^2=5=m 2^2-1^2=5=n\) \(ab=2\)

\(\sqrt{m^2-n^2}/2 = \sqrt{25-9}/2 = 2 = ab\) C

4) -3x^2 + 12x -2y^2 - 12y - 39 MAX \(-3x^2 + 12x\) has max in (2,12) \(-2y^2 - 12y - 39\) has max in (-6,-3) -3x^2 + 12x -2y^2 - 12y - 39 MAX = 12 - 3 =9 D
_________________

It is beyond a doubt that all our knowledge that begins with experience.

1)\(x^4=x^3+6x^2\) \(x^4-x^3-6x^2=0\) \(x^2(x^2-x-6)=0\) \(x^2=0 (1) x = 0\) \(x^2-x-6=0 (2) x = 3 (3) x = -2\) \(0+3-2=1\) C

2)The equation x^2 + ax - b = 0 has equal roots \(a^2+4b=0\) one of the roots of the equation x^2 + ax + 15 = 0 is 3 \((-a+-\sqrt{a^2-4*15})/2=3\) \(+-\sqrt{a^2-60}=6+a\) \((\sqrt{a^2-60})^2=(6+a)^2\) \(-96=12a\) \(a=-8\)

\(a^2+4b=0\) \(64+4b=0\) \(b=-16\) B

3)We can use some numbers \(2^2+1^2=5=m 2^2-1^2=5=n\) \(ab=2\)

\(\sqrt{m^2-n^2}/2 = \sqrt{25-9}/2 = 2 = ab\) C

4) -3x^2 + 12x -2y^2 - 12y - 39 MAX \(-3x^2 + 12x\) has max in (2,12) \(-2y^2 - 12y - 39\) has max in (-6,-3) -3x^2 + 12x -2y^2 - 12y - 39 MAX = 12 - 3 =9 D

Better to post each solution as a separate post, since I cannot give more than 1 kudos point for one post.
_________________

5. I have taken a longer approach, there should be a better solution. x^2 + 2x -15 = -m x^2 + 5x - 3x - 15 = -m (x+5)(x-3) = -m x will have integer values, since m is also an integer. Putting positive values for x such as ( 1, 2....) we will get values for m which lies between -10 and 10, they are -9, 0 and 7. We will get same result for negative values of x, the equation is a parabola, it will be symmetric Hence the probability is 1/3 Answer is B.

Hey, guys, So, I’ve decided to run a contest in hopes of getting the word about the site out to as many applicants as possible this application season...

Whether you’re an entrepreneur, aspiring business leader, or you just think that you may want to learn more about business, the thought of getting your Masters in Business Administration...

Whether you’re an entrepreneur, aspiring business leader, or you just think that you may want to learn more about business, the thought of getting your Masters in Business Administration...